2017
DOI: 10.1002/adfm.201704363
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Broadband Wide‐Angle Terahertz Absorption Properties of 3D Graphene Foam

Abstract: As a next generation of detection technology, terahertz technology is very promising. In this work, a highly efficient terahertz wave absorber based on 3D graphene foam (3DG) is first reported. Excellent terahertz absorption property at frequency ranging from 0.1 to 1.2 THz is obtained owing to faint surface reflection and enormous internal absorption. By precise control of the constant properties for 3DG, the reflection loss (RL) value of 19 dB is acquired and the qualified frequency bandwidth (with RL value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
146
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 262 publications
(147 citation statements)
references
References 47 publications
0
146
0
1
Order By: Relevance
“…When the annealing temperature is 600 °C, I D / I G = 1.62. As an ultralight material, the density of the GF of 600 °C annealing temperature is only 1 mg cm −3 . According to previous research, for samples annealed in the range between 600 and 800 °C, its Fermi level ( E F ) crosses the bandgap, the free carriers change from hole to electrons, and the free carrier density is in the lowest state .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…When the annealing temperature is 600 °C, I D / I G = 1.62. As an ultralight material, the density of the GF of 600 °C annealing temperature is only 1 mg cm −3 . According to previous research, for samples annealed in the range between 600 and 800 °C, its Fermi level ( E F ) crosses the bandgap, the free carriers change from hole to electrons, and the free carrier density is in the lowest state .…”
Section: Resultsmentioning
confidence: 98%
“…For example, Zdrojek et al demonstrated a graphene‐based plastic absorber, and more than 99.99% of the electromagnetic energy is shielded via absorption in the sub‐THz range. The porous materials have a better shielding performance for their larger porosity . For instance, our previous work reported the multiwalled carbon nanotubes doped 3D graphene foam (GF), which has both excellent THz shielding and stealth performance in the THz regime.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the absorbance dominates over the reflectance a lot over for GF and MGF samples in free air. Obviously, the highly porous structure contributes to the ultralow terahertz reflection and also facilitates stronger absorption attenuation due to more interfaces for multiple reflection and scattering …”
Section: Resultsmentioning
confidence: 99%
“…Up till now, stealth materials with porous structures have been often reported in the microwave regime . Recently, our group has been the first to achieve a highly efficient and porous absorber in the terahertz region . However, research on porous terahertz stealth materials is just beginning, and still faces many problems and challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of electronic technologies brings about great convenience to humans' life. However, excessive usage of electronics also results in serious electromagnetic (EM) radiation and interference, which is detrimental to human health [1][2][3][4][5]. Consequently, the research on use of functional EM absorbers to eliminate the unwanted EM energies has attracted significant attention.…”
Section: Introductionmentioning
confidence: 99%